Sexual Harassment and Workplace Bullying on Female Employees in Production Assembly Line - Amirah Izzati, Mohammad Faizzull; Puteri Fadzline, Muhamad Tamyez (Penerbit UTHM, 2021)
Nowadays, mostly in the realities of today's society, the common idea that women should dedicate themselves to household duties is now no longer supportable and their total contributions to the entire workforce and Malaysia’s economy are also vitally essential to the country's economic growth but at the same time the labor force participation has, however, subjected females or women to sexual harassment in their professions (Hassan, 2015). According to Haruna (2016), female employees especially in the manufacturing sector have encountered extreme obstacles into their own workforce but sexual harassment and workplace bullying has become the huge obstacle of consequences spread through physical, mental, behavioral and financial boundaries. This is attributed towards some research that has been undertaken which still continues with reference to the sexuality-based abuse of female operators or production line workers, because, as it might be, there is virtually no review of the deification which consequences of workplace bullying and even sexual harassment within the regulations (Walker, 2018).